An argument for more plurilateral agreements and their value for developing countries: stemming the tide of preferential trade agreements, post-Doha - Houston-McMillan, Jason (Department of Commercial Law, 2017)
The latest round of multilateral trade negotiations at the WTO, the Doha Round, is deadlocked, and it is unlikely that any further significant rule-making progress will be made there. The system's faltering has resulted in an unprecedented move towards preferential trade agreements between WTO Members as alternative negotiating platforms. The result is an ever-expanding divergence of the global trading system, which gives rise to added complexity and wider discrimination than would follow from alternatives - specifically the increased use of plurilateral agreements. Preferential agreements, particularly worryingly, may also have serious consequences for developing and least-developed countries in particular. This paper argues that, in light of the stalling of the Doha Round, greater effort should be made by WTO Members to pursue plurilateral agreements in specific policy areas and to move towards a system incorporating more 'variable geometry' which will result in progress in existing areas which have seen little movement since the Doha Round began. Given the recent proliferation of Preferential Trade Agreements and their potential negative effects on rule-making and the WTO, and on developing countries, it is vital that alternatives are explored in order to promote adaptability which would result in a more effective and relevant WTO.